Passive intervertebral motion characteristics in chronic mid to low back pain: A multivariate analysis. (October 2020) - Brownhill, Kevin; Mellor, Fiona; Breen, Alex; Breen, Alan
Highlights: A multivariate analysis of continuous motion passive inter-vertebral joint kinematic data was carried out. Significant differences between low back pain participants and controls was found for coronal plane motions only. Differences found indicated a compensatory shift of motion to the upper lumbar spine in patients. Abstract: Purpose: Studies comparing back pain patients and controls on continuous intervertebral kinematics have shown differences using univariate parameters. Hitherto, multivariate approaches have not been applied to this high dimensional data, risking clinically relevant features being undetected. A multivariate re-analysis was carried out to estimate main modes of variation, and explore group differences. Methods: 40 participants with mechanical back pain and 40 matched controls underwent passive recumbent quantitative videofluoroscopy. Intervertebral angles of L2/3 to L4/5 were obtained for right and left side-bending, extension, and flexion. Principal components analysis (PCA) was used to identify the main modes of variation, and to obtain a lower dimensional representation for comparing groups. Linear discriminant analysis (LDA) was used to identify how groups differed. Results: PCA identified three main modes of variation, all relating to range of motion (ROM) and its distribution between joints. Significant differences were found for coronal plane motions only (right: p  = 0.02, left: p  = 0.03) . LDA identified a shift in ROM to more cranial joints in the back pain group. Conclusion: The results confirm altered motion sharing between intervertebral joints in back pain, and provides more details about this. Further work is required to establish how these findings lead to pain, and so strengthen the theoretical basis for treatment and management of this condition.